1993
DOI: 10.1677/joe.0.1380159
|View full text |Cite
|
Sign up to set email alerts
|

Glucagon-like peptide-1(7–36)amide and glucose-dependent insulinotropic polypeptide secretion in response to nutrient ingestion in man: acute post-prandial and 24-h secretion patterns

Abstract: The acute effects of different macronutrients on the secretion of glucagon-like peptide-1(7-36)amide (GLP-1(7-36)amide) and glucose-dependent insulinotropic polypeptide (GIP) were compared in healthy human subjects. Circulating levels of the two hormones were measured over a 24-h period during which subjects consumed a mixed diet. In the first study, eight subjects consumed three equicaloric (375 kcal) test meals of carbohydrate, fat and protein. Small increases in plasma GLP-1(7-36) amide were found after all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

11
435
5
4

Year Published

1999
1999
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 607 publications
(461 citation statements)
references
References 0 publications
11
435
5
4
Order By: Relevance
“…We found that delivery of fat calories through the gastrointestinal tract compared with fat delivered directly into the systemic circulation is important for release of GIP, GLP-1, and PYY . Fat content in the diet has been found to be an important trigger for the secretion of these gastrointestinal peptides (14,32,36). However, whereas previous studies have found that dietary fat is a potent stimulus for gastrointestinal peptides secretion, we found a potent reduction in only GIP, with just a modest reduction in GLP-1 and PYY , when most of the fat was removed from the diet.…”
Section: Discussioncontrasting
confidence: 85%
See 3 more Smart Citations
“…We found that delivery of fat calories through the gastrointestinal tract compared with fat delivered directly into the systemic circulation is important for release of GIP, GLP-1, and PYY . Fat content in the diet has been found to be an important trigger for the secretion of these gastrointestinal peptides (14,32,36). However, whereas previous studies have found that dietary fat is a potent stimulus for gastrointestinal peptides secretion, we found a potent reduction in only GIP, with just a modest reduction in GLP-1 and PYY , when most of the fat was removed from the diet.…”
Section: Discussioncontrasting
confidence: 85%
“…However, many of the mechanisms governing gastrointestinal peptide secretion remain unclear. Fat content in the diet has been found to be a trigger for the secretion of these gastrointestinal peptides (14,32,36), but the impact of removing fat calories from the diet on the magnitude of change in the secretion of these peptides is not known.The primary goal of this study was to determine the acute glycemic and endocrine responses to the reduction of fat content from a meal. To better address the influence of ingested fat on postprandial glucose response, subjects ingested tracerlabeled carbohydrate ([ 13 C]glucose) to measure the delivery of the exogenous glucose to the systemic circulation.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…In rats, a greater hyperinsulinaemic response was seen after a 6-week diet enriched in monounsaturated and polyunsaturated fatty acids compared to a diet high in saturated fatty acids [46]. GLP-1 is secreted by the intestinal endocrine Lcells in response to a mixed meal [47], with both glucose and fatty acids being stimulants [48] but circulating and neural mediators could also be important [49]. Plasma active GLP-1 concentrations potentiate glucose-stimulated insulin secretion [50] in a dosedependent manner [49] via GLP-1 receptors on the beta cell.…”
Section: Discussionmentioning
confidence: 99%